Dipyridamole stress echocardiography combined with pair-wise bicycle stress test and transesophageal atrial stimulation in coronary heart disease diagnostics - A. Yu. Vasilyev; N. N. Mikheev (Российский кардиологический журнал)
The aim of the study was to identify and compare informative values of combined high-dose dipyridamole stress echocardiography (EchoCG) and pair bicycle stress test, or transesophageal atrial pacing (TEAP), in coronary stenosis diagnostics. In 118 patients, bicycle stress test and EchoCG with dipyridamole, followed by pair bicycle stress test or TEAP, as well as coronaroangiography, were performed. In all participants, combined stress EchoCG was performed with achieving diagnostic criteria. At coronaroangiography, 31 patients did not have coronary lesion signs; 66 had one-vessel lesions, and 21 - multi-vessel lesions. Validity, sensitivity, and specificity of combined stress EchoCG with dipyridamole and pair bicycle stress test or TEAP, were similar: 94.6% and 94.0%, 100% and 96.5%, 95.1% and 100%, respectively. No correlation of test results with gender was observed. To choose the combination of dipyridamole stress EchoCG and pair bicycle stress test, or TEAP, one should take into account individual tolerance to physical stress.